Farmers' constraints, governmental support and climate change adaptation: Evidence from Guangdong Province, China*. (2nd July 2019) - Xu, Ying; Findlay, Christopher
Abstract : While climate change is widely acknowledged, the role of government support in adaptation is less understood. We narrow this knowledge gap by modelling adaptation as a three‐stage process where a farmer sequentially decides: (i) whether there is a need for adaptation; (ii) whether there are constraints that prevent adaptation; and (iii) whether such constraints are removed through government support. We develop a triple‐hurdle model to describe this decision‐making process and empirically estimate the impact of government support using a rural household survey from Guangdong Province, China. It is found that government support is positively associated with raising the odds of adaptation by about one quarter. This magnitude is larger than the estimates in recent literature, suggesting government support is more effective for farmers bound by constraints. Therefore, for cost‐effective policy outcomes there is a need to identify the constraints and the farmers facing them.